ANALYZING EMPLOYEE ENGAGEMENT TO IMPROVE EMPLOYEE PERFORMANCE AT BNI KC KUNINGAN DURING PARTIAL LOCKDOWN (The Indonesian Journal of Business Administration, 2021)
The VUCA condition caused by the Covid-19 outbreak has significant impact on BNI’s business, including the increase in NPL (non-performing loans) and increasing use of e-money. BNI’s employees are required to work harder to be agile in a VUCA situation. Based on the results of employee performance appraisals in 2020, it is known that the performance of BNI KC Kuningan employees is not satisfactory. This research uses a mixed method, which consists of quantitative and qualitative data. First, researcher conducted a brief inteview to HR Department. Then, conduct a survey. The survey was conducted by distributing questionnaires to 41 samples of BNI KC Kuningan employees. Next, conduct in-depth interviews to confirm the survey results. According to the results of the initial interview, it was found that the cause of unsatisfactory employee performance was the lack of attachment between employees. Furthermore, a survey was conducted to measure the level of employee engagement. For further analysis, the four bottom score need to be improved, include communication between employees and management, recognition of employee performance, employee initiative, and employee effort at work. Then, conduct in-depth interviews to confirm the results of the survey and get the root cause of the problem.Keywords: Employee Engagement, Employee Performance, Communication, Reward and Recognition.